Classroom Management and Novice Language Teachers: Friend or Foe? - Ana Clara Sánchez Solarte (Asociación Colombiana de Profesores de Ingles, 2019)
This article describes the importance of classroom management for language teachers, particularly for novice L2 teachers since it can affect their permanence in the teaching profession. A definition of classroom management along with a description of its dimensions, a set of initial principles and practical ideas to approach teaching with more confidence are provided in this paper. It is expected that this information will contribute to equip inexperienced teachers with procedures and strategies that can be translated and adapted to their teaching situation and ease the transition from student-teacher to being in charge of a classroom on their own.